UTILIZATION OF PINEAPPLE WASTE AS CARBON SOURCE - Abdullah Moch Busairi (Dept. of Chemical Engineering, Diponegoro University, 2009)
The liquid pineapple waste contains mainly sucrose, glucose, fructose and other nutrients. It therefore can potentially be used as carbon source for organic acid fermentation. The objective of this work is to evaluate the use of pineapple waste as substrate for lactic acid fermentation under variables of aerobic, anaerobic condition and pH controlling. Initial results showed that the liquid pineapple waste can be used as carbon source for lactic acid fermentation using Lactobacillus delbrueckii. In the anaerobic condition growth of bacteria and lactic acid production better than aerobic condition. In the anaerobic condition and the controlled pH the production of lactic acid are found to be 54.79 g/l (78.27% yield) at 40oC, pH 6, 50 rpm and 70 g/l sugar concentration. In contrast, only 13.87g/l lactic acid produced if the fermentation pH was not controlled even though the fermentation parameters were kept at the same conditions